The Relationship between Mental Workload and Occupational Stress among Aircraft Maintenance Officers at PT X - Fauziah Mukti Sugiharto (Universitas Airlangga, 2019)
ABSTRACTIntroduction: Aircraft maintenance officer is one of the professions which is prone to work stress, because it requires abundant amount of knowledge and skills, as well as rapidity and accuracy in completing the task. Moreover, poor work environments such as noise, vibration, and extreme temperature also add to more workload and trigger occupational stress. This research aims to identify the relationship between mental workload and occupational stress on the aircraft maintenance officers at PT. X. Metods: This research was a descriptive observational research with cross-sectional design. The sample in this research was the total population of officers at PT. X, comprising 21 engineers and 20 mechanics. The total of 41 officers was used as the respondents in this research. The data of mental workload was collected using NASA-TLX method and Brief Job Stress Questionnaire was used to measure occupational stress among aircraft maintenance officers at PT. X. Results: The results of this study demonstrated that most officers had a heavy level of mental workload and experienced a moderate level of occupational stress. The Spearman-rho correlation test showed that there was a moderate relationship between mental workload and occupational stress (r = 0.306). Conclusion: It can be concluded that there was a relationship between mental workload and occupational stress among aircraft maintenance officers at PT. X. Keywords: aircraft maintenance officer, mental workload, occupational stress